KAJIAN HUBUNGAN MODAL SOSIAL DENGAN KEMISKINAN NELAYAN BAGANG DI DESA LABEAN KECAMATAN BALAESANG KABUPATEN DONGGALA - Nasruddin, M. Anwar (Katalogis, 2017)
This study aims to determine the characteristics of social capital and poverty in fishing communities of boat lift nets fisherman and to aknowledge the relationship between the variables of social capital and poverty in fishing communities of boat lift nets in Labean Village. This research is categorised as descriptive quantitative. This study intends to get a description and a picture of the social capital relationships with poverty of fishing communities of boat lift nets. This study was conducted in 2015 and the data were collected by using: observation, interviews, literature and documentation. Then, the data were analyzed by several methods of analysis, namely: 1) The characteristics of social capital of fishing communities of boat lift nets in Labean Village are categorised as middle category on average. It indicates that fishing communities of boat lift nets haveÂ good social capital. Especially, the social capital related to the level of reciprocity and proactivity. 2) The characteristics of poverty or the level of prosperity of of fishing communities of boat lift nets in Labean Village have alsoÂ middle category. However, this midlle category on the property and prosperity level is categorised as low level (unsecure) and;3) according to statistical results show that chi-square level is 2.861, with P value is 0.091. The results also show that the P-value is less than Î±=10%, so that there is correlation between social capital and proverty or the level of prosperity ofÂ fishing communities of boat lift nets in Labean Village in Balaesang District.